EASTERN SURGERY IN MANUSCRIPT SOURCES IN THE COLLECTION OF THE INSTITUTE OF MANUSCRIPTS OF THE NAN OF AZERBAIJAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
For many centuries, scientists, creating scientific works in various fields, have enriched world science and culture and thereby contributed to their development. Analysis of existing sources gives grounds to assert that a new culture, a new civilization was formed in the Muslim Middle Ages. The history of medicine, being an integral part of the common human culture, was formed against the background of the general historical development of society according to the laws common to any science. And it is generally known that this era, full of the greatest discoveries and bringing up outstanding scientists - encyclopedists, known to the whole world, was called the era of the "Muslim Renaissance "[1,71].